A historical overview of the general implementation of the European Union Market Abuse Directive in the United Kingdom before Brexit and its future implications. Issue 2 (April 2017) - Chitimira, Howard
The European Union (EU) was arguably the first body to establish multinational anti-market abuse laws aimed at enhancing the detection and curbing of cross-border market abuse activities in its Member States. Put differently, the EU Insider Dealing Directive was adopted in 1989 and was the first law that harmonized the insider trading ban among the EU Member States. Thereafter, the European Union Directive on Insider Dealing and Market Manipulation (EU Market Abuse Directive) was adopted in a bid to improve and effectively discourage all forms of market abuse in the EU's securities and financial markets. However, the EU Market Abuse Directive had its own gaps and flaws. In light of this, the Market Abuse Regulation and the Criminal Sanctions for Market Abuse Directive were enacted to repeal and replace the EU Market Abuse Directive in 2016. The article examines the adequacy of the EU Market Abuse Directive and its implementation in the United Kingdom (UK) prior to the UK's vote to leave the European Union (Brexit). This is done to investigate the possible implications of the Brexit referendum outcome of 23 June 2016 on the future regulation of market abuse in the UK.